Formulasi dan bioaktivitas suplemen tablet berbasis Spirulina dan hidrolisat kolagen kulit ikan nila - Mirza Gulam Ahmad; Iriani Setyaningsih; Wini Trilaksani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Spirulina is a microalga known as a superfood which contains high protein and is used in cosmetics, foods, and supplements industry. Collagen hydrolysate is the result of hydrolysis of collagen by protease. This study was aimed to determine the antioxidant activity and inhibition of tyrosynase from Spirulina, collagen hydrolysate and tablet formulated by combination of Spirulina and collagen hydrolysate. This research was conducted in three stages. The first stage was the extraction and hydrolysis of tilapia skin collagen, while the second stage was culturing and harvesting of Spirulina, and the third stage was determination of tablet formulation based on Spirulina and collagen hydrolysate followed by analysis of the antioxidant activity and inhibition of tyrosinase by selected tablet. Three formula with different ratio between Spirulina and collagen hydrolysates namely formula A (25%:53.75%), formula B (28.125%:50.625%), formula C (31.25%:47.5%) and additive such as vitamin C (12.5%), talk (1.25%), magnesium stearate (0.625%), aerosil (1.875%), avicel (5%) were developed. The result showed that formula A was the selected formula meeting the requirements of Ministry of Health based on the physical characteristics. The antioxidant activity of tablet A was 843 ppm and the tyrosinase inhibition was 163.56 ppm.